SAMURAI (Mosquito Repellent Spray Made from Lemongrass) Training - Sugiarto, Amelia Finnahar Putri; Kalyana, Harrel Atha; Ramadhan, Rafly Satria; Salsabila, Alifatus; Hasna, Ade Fairus; Irwansyah, Dani; Jizmi, Ukhti Qowwiyul; Patria, Sadam Mulia; Nuraeni, Nadya Intan; Fajro, Annisa Shofia; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. This disease remains a major health problem in Indonesia, with high annual dengue cases. As the number of dengue cases increases in Indonesia, many companies are producing various mosquito repellent products, tools, and medications. However, many of these products are environmentally unfriendly and may have negative impacts on public health, such as mosquito coils containing pesticides. As part of their community service efforts, KKN students are educating the public on how to prevent dengue fever by teaching them about herbal plants that can be used to repel mosquitoes. Lemongrass was chosen as the plant because mosquitoes dislike its smell, and it is easily found in the surrounding area, especially in the Peniron area of Kebumen. These leaves can easily be processed into a spray that naturally repels mosquitoes because the smell of lemongrass leaves is disliked by mosquitoes. In addition to being good for health, this SAMURAI product can also be used as a new product to be sold as a new business in the village where the KKN takes place.